The Preventive Effects of Greenshell Mussel (Perna canaliculus) on Early-Stage Metabolic Osteoarthritis in Rats with Diet-Induced Obesity - Siriarchavatana P; Kruger MC; Miller MR; Tian HS; Wolber FM (MDPI (Basel, Switzerland))
The prevalence of osteoarthritis (OA) is rising worldwide, with the most pronounced increase being in the category of metabolic-associated osteoarthritis (MetOA). This is predicted to worsen with the global rise in aging societies and obesity. To address this health burden, research is being conducted to identify foods that can reduce the incidence or severity of MetOA. Oil from the Greenshell mussel (Perna canaliculus) (GSM), a native New Zealand shellfish, has been successfully used to reduce OA symptoms. The current study assessed the effect of including flash-dried powder from whole GSM meat as part of a normal (control) versus high-fat/high-sugar (HFHS) diet for 13 weeks on the development of MetOA in rats. Rats fed a HFHS diet developed metabolic dysregulation and obesity with elevated plasma leptin and HbA1C concentrations. Visible damage to knee joint cartilage was minimal, but plasma levels of C telopeptide of type II collagen (CTX-II), a biomarker of cartilage degradation, were markedly higher in HFHS-fed rats compared to control-fed rats. However, rats fed the HFHS diet containing GSM had significantly reduced serum CTX-II. Inclusion of GSM in rats fed the control diet also lowered CTX-II. These findings suggest that dietary GSM can reduce the incidence or slow the progression of early MetOA.
Keywords: osteoarthritis; metabolic dysregulation; obesity; diet-induced obese rats; Greenshell mussel; Perna canaliculus; 0908 Food Sciences; 1111 Nutrition and Dietetics